Analysing formal models of genetic regulatory networks with delays. (18th July 2008) - Ahmad, Jamil; Roux, Olivier; Bernot, Gilles; Comet, Jean-Paul; , Adrien Richard
In this paper, we propose a refinement of the modelling of biological regulatory networks based on the discrete approach of Rene Thomas. We refine and automatise the use of delays of activation/inhibition in order to specify which variable is more quickly affected by a change of its regulators. The formalism of linear hybrid automata is well suited to allow such refinement. We then use HyTech for two purposes: to find automatically all paths from a specified initial state to another one; to synthesise constraints on the delay parameters in order to follow any specific path.